P-537 PRIMARY SEX RATIO IS DECREASED IN EUPLOID EMBRYOS OF CONSANGUINE COUPLES AFTER IVF/ICSI WITH PGT-A. (30th June 2022) - Nogueira, D; Fatemi, H; Lawrenz, B; Elkhatib, I; Abdala, A; Bayram, A; Ahmed, E.D; Melado, L
Abstract: Study question: What is the primary sex ratio outcome of embryos from consanguine couples as per PGT-A analysis during IVF/ICSI treatments? Summary answer: The primary sex ratio (PSR) (males-to-females) is decreased in euploid blastocysts from consanguine couples. What is known already: In the general population, the sex ratio (males-to-females) tends to be 1:1 (approximately 101 males to 100 females). In epidemiological studies secondary sex-ratio (ratio at the time of birth) of inbred-offspring seems to be equilibrated. However, it is well known that there is an increased incidence of autosomal recessive diseases for the offspring, compared to non-consanguineous couples. Studies have found elevated autosomal inheritances as compared to sex-linked inheritance. Assessing the impact of consanguinity on developed embryos might contribute to the understanding of the events leading to genetic diseases. Study design, size, duration: This analysis includes data from 5135 blastocysts after preimplantation genetic testing for aneuploidy (PGT-A) with NGS. Embryos were obtained from 1836 IVF/ICSI cycles of infertile couples, at ART Fertility Clinics UAE, from November 2016 to December 2020. Consanguinity was defined when couple were first-degree or second-degree cousins. Participants/materials, setting, methods: A total of 1138 blastocysts from consanguine couples, and 3997 from non-consanguine couples were included in the analysis. All blastocysts presented normal sexual chromosome constitution with or without autosomal aneuploidies. Mosaic and non-informative embryos were excluded. Trophectoderm biopsy was performed on day 5 for PGT-A using Next Generation Sequencing (NGS) platform. Primary sex ratio (PSR) was observed for CG and NCG couples. Ethical approval was obtained from the Research Ethics Committee (REFA023b). Main results and the role of chance: In consanguine couples the age of female and male partner was 30.7±5.5 and 35.9 ±5.3 years old, respectively; while non consanguine couples were older (32.2±5.8 and 37.6±7.3 years old, respectively) (p < 0.001). Expanded blastocysts deriving from consanguine couples had 52.3% of XX versus 47.7% of XY constitution of their trophectoderm biopsied cells, presenting thus a significant decrease in primary sex ratio (PSR: 0.91, p = 0.03). In non-consanguine couples, about 51.2% of trophectoderm biopsied cells had a XX constitution compared to 48.8% of XY constitution, presenting a PSR of 0.95 (NS). The significant decreased PSR in consanguine couples was only related to normal euploid embryos and not to abnormal embryos (PSR of abnormal embryos = 0.98; NS). Euploid embryos from couples presenting consanguinity generated 53.4% of blastocysts of XX constitution versus 46.6% of XY constitution with a PSR at 0.87 (p = 0.01). Euploid embryos from non-consanguine couples presented a PSR at 0.96 (p=NS) (50.9% blastocysts of XX constitution versus 49.1% with XY constitution). Limitations, reasons for caution: Differences in PSR between consanguine and non-consanguine couples did not reach significance level, justified by the lower number of embryos derived from consanguinity compared to non-consanguinity couples. Moreover 85% of the population included derives from Arabian Peninsula, therefore these results should not be transposed to other consanguine populations. Wider implications of the findings: It is known that consanguine couples derive embryos with increased abnormalities in comparison to the general population. The fact that euploid embryos from consanguine couples seems to present a higher female constitution might incite us to investigate to what extent does heterozygosity for x-linked loci contribute to embryo survival. Trial registration number: not applicable